Organization of risk management during implementation investment and innovative projects - E. A. Bogomolova; N. V. Vozgoment (Вестник университета)
The approaches to risk determination, methods of its assessment, standardization parameters of investment activity and its stages have been considered. The key moments in the organization of risk management at the enterprise have been highlighted. The technologies of qualitative and quantitative assessments of the organization of risk management at the enterprise have been identified. The estimation of the fragmentation of risk management in the current market conditions has been conducted. Off rs on implementationn of the most constructive and complex approaches to the organization of risk and management at the enterprise have been given.